Three-phase bio-nanocomposite natural-rubber-based microfibers reinforced with cellulose nanowhiskers and 45S5 bioglass obtained by solution blow spinning - Silva, Michael J. [UNESP]; Dias, Yasmin J.; Zaszczyńska, Angelika; Kołbuk, Dorota; Kowalczyk, Tomasz; Sajkiewicz, Paweł Ł.; Yarin, Alexander L. (Wiley, 2023)
Aiming at biomedical applications, the present work developed a new bio-nanocomposite fibrous mat based on natural rubber (NR) reinforced with 45S5 bioglass particles (BG) and cellulose nanowhiskers (CNW), which reveals excellent mechanical properties, good biocompatibility and bioactivity properties. Analyses of the specimens were conducted by means of morphological observations (SEM) and thermal analysis (TG/DTG), as well as mechanical tests used to verify the effect of the incorporation of BG particles and CNW on the ultimate properties of these flexible NR-CWN/BG fibrous membranes. An SEM analysis revealed that all filaments possessed a ribbon-like morphology, with increasing diameters as the BG concentration increased. This likely results from an increased viscosity of the solution used for fiber blowing. In comparison with neat NR fibrous mats, the ultimate mechanical properties of bio-nanocomposites were significantly improved due to the presence of CNW and BG particles dispersed in the NR matrix. According to the TG/DTG analysis, the specimens' thermal stability was unaffected by the high BG content, and the thermal profiles were similar, with isoprene chains decomposition of the NR occurring between 350 and 450°C. In-vitro analysis on fibroblasts confirmed that the bio-nanocomposite fibrous mats are noncytotoxic. It was found that fibrous mats enhanced cellular growth and hold great promise for tissue engineering applications.
Keywords: bioactive particles; cellulose nanowhiskers; fibrous mat bio-nanocomposite; natural rubber; solution blow spinning